Fracionamento de bagaço de cana-de-açúcar combinando tratamentos com solvente eutético profundo e ácido diluído - Souza, Layanny Samara da Silva (2023)
The Brazilian sugar and alcohol industry generates more than 640 million tons of sugarcane annually and approximately 180 million tons of sugarcane bagasse. The use of bagasse to produce second-generation ethanol can increase the national production capacity of ethanol. For this purpose, it is necessary to break the recalcitrant structure of the biomass, preferably taking advantage of the generated lignin and hemicellulose fractions, in a biorefinery context. In this work, treatment with a deep eutectic solvent based on choline chlorine and urea was followed by hydrolysis using dilute sulfuric acid for the removal of lignin, conversion of hemicellulose into fermentable xylose and beneficiation of bagasse by increasing its cellulose content. The first treatment extracted 50% of the lignin present and the resulting delignified biomass, chosen from 34% cellulose, 12% lignin and 19% hemicellulose, was used to optimize acid hydrolysis through a Central Composite Experimental Design, optimizing the sulfuric acid concentration and reaction time. The proposed quadratic mathematical model presented R2 = 0.94 and explained 93.8% of the variation in the experimental data, with the quadratic contributions of acid and time, the linear contribution of acid and the linear combination of the two factors being manifested, with 5% of uncertain statistics. The optimum point corresponded to 1.1% sulfuric acid and a time of 59 min 24 s. The hydrolyzed liquor obtained under these conditions presented 18 g L-1 of xylose without the presence of fermentation inhibitors and the final biomass residue had its cellulose content increased to 51%, due to the removal of lignin and hemicellulose, which now represents 16 % and 8% of the composition, respectively. The increase in the proportion of cellulose resulted in an increase in the crystallinity index, which went from 55% in the in natura sample to 58% after lignin removal and 64% after acid hydrolysis. When applying the optimal conditions of hydrolysis to the biomass in natura, concentrations of xylose and cellulose similar to those obtained in the hydrolysis of the biomass treated with the eutectic solvent were found, however the concentration of lignin, the most recalcitrant component, was preserved in 24%, not having been recovered separately. The combined treatment of lignin extraction by eutectic solvent with acid hydrolysis was successful in the separation of the fractions, with removal of about 50% of the lignin from the bagasse, 96% of efficiency of conversion of hemicellulose into xylose and approximately 40% of increase in the content of content cellulose.